Inflation and infrastructure sector returns in emerging markets: Panel ARDL approach - Rabson Magweva; Mabutho Sibanda (Cogent Economics & Finance, 2020)
This study evaluated the relationship between inflation and infrastructure sector stock returns in emerging markets in the long and short run. It employed a panel autoregressive distributed lag (PARDL) model applying the mean group (MG), pooled mean group (PMG) and dynamic fixed effects (DFE) estimators after preliminary cross-sectional dependence and stationarity tests. The results from the three estimators were insignificant in both the short and long run, illustrating the inability of infrastructure sector returns in emerging markets to hedge inflation. Similar results were obtained when the inflation-hedging capacity of real estate and general listed equity was assessed. This suggests the existence of significant beta risk in emerging stock markets. The results imply that investors interested in hedging inflation in emerging markets should go beyond individual asset classes and embrace the portfolio optimization concept to reduce inflation risk. Given the heterogenic nature of the infrastructure sector, a deeper analysis that focuses on infrastructure sector sub-categories might be fruitful as the pricing power is heterogeneous across these sub-sectors.
Keywords: E31; H54; C33; G11; O50; 330; inflation; infrastructure; pooled mean group; beta risk; portfolio optimization